Sheep Displayed No Clinical and Parasitological Signs upon Experimental Infection with Babesia aktasi - Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Mdpi, 2024)
Simple Summary: In this study, an experimental investigation was conducted to assess the pathogenicity of Babesia aktasi in immune-suppressed sheep. For this purpose, five immune-suppressed lambs under one year of age were infected by intravenous injection of fresh blood containing approximately 9.2% and 12% parasitemia of B. aktasi. Following parasite injection, the lambs were monitored daily for clinical and microscopic findings of babesiosis for 30 days. Throughout this period, no clinical and microscopic signs of babesiosis were observed in the lambs. Of the five recipient lambs, two tested negative for B. aktasi in nested PCR up to 30 days post-infection. Among the remaining three lambs, two were PCR positive on the first day, and the other one remained positive until the fourth day post-infection. DNA sequencing confirmed that the PCR positivity in the recipient lambs originated from the inoculum. These findings indicate that immune-suppressed lambs do not appear to be susceptible to infection with B. aktasi, which is highly pathogenic to immune-suppressed indigenous goats. Our survey in the Mediterranean region of T & uuml;rkiye revealed high prevalence of Babesia aktasi in goats, while no molecular evidence of the parasite was found in sheep grazing in the same pasture. We hypothesized that the parasite may not be infectious to sheep. To test this hypothesis, the present study was designed to evaluate the susceptibility of Akkaraman sheep breed to B. aktasi infection. Fifteen mL of fresh blood infected with B. aktasi was injected into immune-suppressed lambs (n = 5). The recipient lambs were monitored daily for clinical signs of babesiosis over 30 days, and blood was collected for microscopic and molecular diagnostic evaluation. The lambs did not display clinical and parasitological signs of babesiosis. Two out of five recipient lambs were nested PCR-negative for B. aktasi over 30 days post infection. Out of the remaining three lambs, two were PCR positive on the first day, and one recipient was positive until the fourth day post infection. DNA sequencing confirmed that the PCR positivity in the recipient lambs originated from the inoculum. These findings revealed that immune-suppressed sheep do not appear to be susceptible to infection with B. aktasi that is lethal to immune-suppressed indigenous goats.
Keywords: Babesia aktasi; experimental study; sheep; pathogenicity